2014
DOI: 10.1038/nature13474
|View full text |Cite
|
Sign up to set email alerts
|

Lipid landscapes and pipelines in membrane homeostasis

Abstract: The lipid composition of cellular organelles is tailored to suit their specialized tasks. A fundamental transition in the lipid landscape divides the secretory pathway in early and late membrane territories, allowing an adaptation from biogenic to barrier functions. Defending the contrasting features of these territories against erosion by vesicular traffic poses a major logistical problem. To this end, cells evolved a network of lipid composition sensors and pipelines along which lipids are moved by non-vesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
691
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 739 publications
(735 citation statements)
references
References 95 publications
15
691
0
2
Order By: Relevance
“…Secretion and sphingolipid homeostasis are co-regulated, however little is known about how a vesicular trafficking defect may impact lipids homeostasis. 27,28 Here we found that transport of exogenous GPI-anchored proteins to the PM is inhibited and that the endogenous GPIanchored cellular Prion protein (PrPc) accumulated in the Golgi apparatus in VAMP7 KO fibroblasts. Furthermore we found that the dynamics of the Golgi apparatus after treatment by Brefeldin A and washout was impaired in VAMP7 KO cells.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Secretion and sphingolipid homeostasis are co-regulated, however little is known about how a vesicular trafficking defect may impact lipids homeostasis. 27,28 Here we found that transport of exogenous GPI-anchored proteins to the PM is inhibited and that the endogenous GPIanchored cellular Prion protein (PrPc) accumulated in the Golgi apparatus in VAMP7 KO fibroblasts. Furthermore we found that the dynamics of the Golgi apparatus after treatment by Brefeldin A and washout was impaired in VAMP7 KO cells.…”
Section: Introductionmentioning
confidence: 92%
“…Further glycosylations then occur on monoglycosylated ceramides, in different Golgi subdomains, 26 to give rise to a large variety of complex glycosphingolipids (GSL) which are then transported along the secretory pathway and particularly to the PM. Sphingolipid biosynthesis and turnover are regulated with cell growth and they travel via both vesicular and non-vesicular transports from ER to Golgi, and mainly via vesicles from Golgi to PM, (for reviews see 27,28 ). Secretion and sphingolipid homeostasis are co-regulated, however little is known about how a vesicular trafficking defect may impact lipids homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acids form the hydrophobic tails of membrane phospholipids (Piomelli et al 2007;Assies et al 2014;Holthuis and Menon 2014). Double bonds cause curvatures in (poly)unsaturated fatty acids.…”
Section: Neuronal Membrane Structurementioning
confidence: 99%
“…The fluidity of the membrane influences lipid-protein interactions of membrane-bound proteins as neurotransmitter-receptors and -transporters (Fisar 2005;Rituper et al 2010;Pengcheng Fan 2015). Thereby, (neuronal) membrane fatty acid composition can influence synaptic communication, providing an important potential pathway through which fatty acids may be involved in neuronal connectivity and thereby in psychiatric disorder pathophysiology (Piomelli et al 2007;Assies et al 2014;Holthuis and Menon 2014). As an example, the geometrical characteristics of fatty acids in the presynaptic membrane have been suggested to facilitate exocytosis of neurotransmittercontaining synaptic vesicles (Piomelli et al 2007).…”
Section: Neuronal Membrane Structurementioning
confidence: 99%
“…Membrane fluidity is promoted by lipids with short, unsaturated fatty acids [57]. In DMD If it is difficult to distinguish between a causal role of cardiolipin and a correlative effect, in one study, replenishment with cardiolipin of hypothyroid mitochondria restored the activity of cytochrome oxidase to control levels [60].…”
Section: Myostatin and Membrane Phospholipids Compositionmentioning
confidence: 99%